2009
DOI: 10.1182/blood-2009-03-211797
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of myelodysplastic syndrome patients with erythropoietin with or without granulocyte colony-stimulating factor: results of a prospective randomized phase 3 trial by the Eastern Cooperative Oncology Group (E1996)

Abstract: This phase 3 prospective randomized trial evaluated the efficacy and long-term safety of erythropoietin (EPO) with or without granulocyte colony-stimulating factor plus supportive care (SC; n ‫؍‬ 53) versus SC alone (n ‫؍‬ 57) for the treatment of anemic patients with lower-risk myelodysplastic syndromes. The response rates in the EPO versus SC alone arms were 36% versus 9.6%, respectively, at the initial treatment step, 47% in the EPO arm, including subsequent steps. Responding patients had significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 42 publications
5
117
0
6
Order By: Relevance
“…Systematic reviews and meta-analyses of studies of ESAs in MDS patients and a recent phase III trial showed ESAs to have potentially clinically important anemia-ameliorating activity in subsets of MDS patients. 12,22,23 Unlike anemic patients with epithelial malignancy, ESA-treated MDS patients rarely achieve normal levels of hemoglobin. Few studies raised a question of safety in terms of increased risk of thrombosis as MDS patients have a low baseline risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews and meta-analyses of studies of ESAs in MDS patients and a recent phase III trial showed ESAs to have potentially clinically important anemia-ameliorating activity in subsets of MDS patients. 12,22,23 Unlike anemic patients with epithelial malignancy, ESA-treated MDS patients rarely achieve normal levels of hemoglobin. Few studies raised a question of safety in terms of increased risk of thrombosis as MDS patients have a low baseline risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The FDA released a Public Health Advisory in 2007 and ESA product labels were updated to reflect this risk, with a recommendation that ESA therapy be suspended when hemoglobin (Hb) levels reach 12 g/dL or rise more than 1 g/dL per week. 11 There are few reports of thrombosis in clinical trials of ESAs in the MDS patient population; one DVT was reported in a patient in the treatment arm in the ECOG study 12 and 4 patients (2%) in a single arm treatment study of DARBO had a thromboembolitic or "related events". 13 There are also a limited number of case reports of thrombosis among MDS patients exposed to ESAs.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of GCSF (lenigrastim) has improved the response rate to approximately 40%, particularly for patients with ring sideroblasts (Negrin et al, 1996;Hellstrom-Lindberg et al, 1997Casadevall et al, 2004). Although increased erythroid responses have been noted with the addition of GCSF to EPO as well as with increased EPO doses (Greenberg et al, 2009b), a meta-analysis of data using these regimens demonstrated higher responses with the drug combination mainly in patients with relatively lower dose EPO monotherapy (Mundle et al, 2009). Darbepoetin (a longer acting version of EPO) has demonstrated similar and perhaps improved efficacy at doses of 150-300 lg sc every 1-2 weeks (Musto et al, 2005;Stasi et al, 2005;Mannone et al, 2006;Gotlib et al, 2008).…”
Section: Management Of Lower Risk Diseasementioning
confidence: 99%
“…Based on currently available evidence, progression to leukemia is unlikely to be the result of epoetin treatment. A prospective clinical trial of ESAs in MDS (ECOG E1996 trial) evaluated the efficacy and long-term safety of epoetin, with or without granulocyte colony-stimulating factor plus supportive care (SC; n=53) vs. SC alone (n=57) for the treatment of anemic patients with lower-risk MDS (18). The presence of older patients with more comorbidities and the lack of data regarding basal serum epoetin level may explain the marginally worse time-to-response to epoetin and the most frequent administration of maintenance epoetin dose in group A.…”
Section: Discussionmentioning
confidence: 99%